WIRELESS DATA ACQUISITION SYSTEM USING BLUETOOTH TECHNOLOGY FOR INFRASONIC RECORDS - Chilo, José; Lindblad, Thomas (International Journal of Computing, 2014)
Advancements in electronics provide a vital new option for implementation of low-frequency smart sensors that can perform signal processing close to the sensors and transmit the data wirelessly. These smart sensors can improve the efficiency of an automatic classification system and reduce the cost of actual infrasound microphones. The design of a digital wireless data acquisition system using a QF4512 programmable signal converter from Quickfilter Technologies, a MSP430 microcontroller from Texas Instruments and a F2M03GLA Bluetooth module from Free2move for infrasonic records is presented in this paper. The digital wireless data acquisition system has passed extensive laboratory and field tests (e.g. with man-made explosions).